The health workers formal education in the field of biophysics and medical physics in the Republic of Serbia and the region - Stanković, Jovan; Mirkov, Zoran; Dabić-Stanković, Kata; Trokić, Danijela; Đukanović, Nina (Education and Research in Health Sciences, 2025)
The modern medicine involves the application of sophisticated diagnostic and therapeutic procedures that are based on discoveries from other scientific fields (biology, chemistry, physical chemistry, physics, mathematics, statistics, informatics, etc.) which makes it multidisciplinary. All these scientific fields can be united in one field biophysics, the physics of living nature at all levels: molecular, cellular and supracellular. Contemporary biophysics deals with examination of the structure and functioning of biological systems, data analysis (from biological/medical experiments), model formation, neuroscience, bioengineering, robotics, medical imaging and other medical applications, and the effect of physical and physicochemical agents on biological systems/people as well as the response of the system to the action of those agents. Within the applied studies in the field of medicine (health studies), after the educational reform, some forms of teaching in the subjects of Biophysics, Medical Physics and Physics of the Human Body have been retained, which enables students to acquire basic knowledge and understand the importance of this scientific field, especially when it comes to the application of modern diagnostic and therapeutic methods, which, in addition to the benefits for the patient, can have certain unwanted effects on patients, as well as medical workers and the environment.
Keywords: biophysics; medical physics; theranostics; radiomics; teaching; educational reform